2023
DOI: 10.1093/ijnp/pyad004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-HT1A Receptor Partial Agonists of the Azapirone Class as an Add-On Therapy on Psychopathology and Cognition in Schizophrenia: A Systematic Review and Meta-Analysis

Abstract: Background There are ongoing efforts to examine the effect of 5-HT1A receptor partial agonists as an add-on therapy for several symptoms of schizophrenia. By conducting a systematic review and meta-analysis, we evaluated whether augmentation with 5-HT1A partial agonists of the azapirone class improves psychotic symptoms and attention/processing speed, a key domain of cognition, in patients with schizophrenia. Methods A litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Our search identified one positive study on Buspirone by Wang et al 46 It includes 196 patients and demonstrated that co‐treatment of buspirone with atypical antipsychotics outperformed atypical antipsychotics alone in improvements in logical reasoning, generalization, visual discrimination/memory/comprehension, and spatial coordination in patients with schizophrenia, supporting the notion that cognitive dysfunction in schizophrenia may be alleviated through 5‐HT1A stimulation. A recent meta‐analysis in this area suggested that buspirone can improve attention and processing speed in patients with schizophrenia 47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search identified one positive study on Buspirone by Wang et al 46 It includes 196 patients and demonstrated that co‐treatment of buspirone with atypical antipsychotics outperformed atypical antipsychotics alone in improvements in logical reasoning, generalization, visual discrimination/memory/comprehension, and spatial coordination in patients with schizophrenia, supporting the notion that cognitive dysfunction in schizophrenia may be alleviated through 5‐HT1A stimulation. A recent meta‐analysis in this area suggested that buspirone can improve attention and processing speed in patients with schizophrenia 47 …”
Section: Resultsmentioning
confidence: 99%
“…A recent meta‐analysis in this area suggested that buspirone can improve attention and processing speed in patients with schizophrenia. 47 …”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with previous research findings. A recent meta-analysis showed that buspirone can help improve attention in patients with schizophrenia [ 50 ]. As a 5-HT1A receptor agonist, the potential mechanism of the cognitive benefits of buspirone may be related to the activation of 5-HT1A receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of the 5-HT 1A receptor often interferes with memory-encoding mechanisms in brain, which leading to learning disabilities. However, antagonists of 5-HT 1A receptor can enhance cortical cholinergic/hippocampal and/or glutamatergic neurotransmission, which promoting certain types of memory ( Ogren et al, 2008 ; Yamada et al, 2023 ). 5-HT 1A antagonists reversed the cognitive impairment induced by NMDA receptor antagonists or mACh receptor antagonists ( Luttgen et al, 2005 ; Madjid et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%